Neurodevelopment and Neurodevelopmental Disorder - Fitzgerald, Michael (Physiology, 2019)
Nowadays, neurodevelopmental disorders comprise a large proportion of mental health diagnoses. These disorders, according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, include intellectual disabilities, communication disorders, autism spectrum disorders, attention deficit hyperactivity disorders, specific learning disorders, and motor disorders. Current research is pointing in the direction of schizophrenia, bipolar disorders, and other disorders being included in the category of neurodevelopmental disorders as well. There is a great deal of overlap among these disorders and they are best understood in a dimensional fashion. This book sets out the future of psychiatry in relation to these disorders and what is basically a new understanding of psychiatry in recent decades. Chapters cover topics such as early recognition of schizophrenia, epilepsy, and the genetics of ataxia telangiectasia. Also included is an examination of the complex issue of systems biology and neurodevelopment.